Dermoscopy and the experienced clinicians. (20th June 2019) - Conforti, Claudio; Giuffrida, Roberta; Vezzoni, Roberta; Resende, Fernanda S.S.; di Meo, Nicola; Zalaudek, Iris
Abstract: For several decades, melanoma diagnosis was based on symptoms rather than clinical features. In fact, until the 1970s melanoma was widely not recognized and only diagnosed when presenting as a large, ulcerated, and bleeding nodule. Today it is well known that ulceration and bleeding are symptoms of an advanced stage; thus, it comes not as a surprise that the prognosis of melanoma at that time was very poor. This paper was developed to recognize dermoscopy as an integrative part of the clinical examination, bearing in mind that naked eye diagnosis can change after dermoscopy outcomes, and to help clinicians avoid the concept: "If in doubt, cut it out".